Allelic Variation of Wheat Flour Allergens in a Collection of Wheat Genotypes - D. Nigro; S. L. Giove; S. Fortunato; O. Incerti; S. A. Zacheo; A. Blanco; A. Gadaleta (Journal of Chemistry)
Wheat is the most widely grown crop in the world and provides 20% of the daily protein and food calories for 4.5 billion people. Together with rice, it is the most important food crop in the developing world. In the last decades, various symptoms have been recorded across the population due to the consumption of wheat products, also summarized as “wheat allergy.” Wheat allergy is usually reported as a food allergy but can also be a contact allergy as a result of exposure to wheat. Several important wheat allergens have been characterized in the last years through biochemical, immunological, and molecular biological techniques. In the present work, the identification of allelic variation of genes involved in wheat allergy was reported. A collection of wheat genotypes was screened in order to identify new alleles. A total of 14 new alleles were identified for profilin, triosephosphate-isomerase, dehydrin, glyceraldehyde-3-phosphate-dehydrogenase, α/β gliadin, GluB3-23, and Glutathione transferase allergen genes (located on chromosomes 1B, 3B, 6A, and homoelogous groups 5 and 7), potentially related to a minor allergenicity and useful in breeding programs.